Challenges and Opportunities of Public Health Professionals in Nepal: A Reflexive Thematic Analysis - Ankit Acharya; Romika Neupane; Bibekti Nepal; Liberty Shrestha; Princy Bhatta (Public Health Challenges, 2026)
ABSTRACT Background Public health professionals (PHPs) constitute a critical component of health systems, but their ability to apply knowledge effectively across sectors is often constrained. Persistent issues such as inadequate training, limited career opportunities, and job dissatisfaction undermine workforce effectiveness and retention globally. In Nepal, these challenges are compounded by weak alignment between academic preparation and professional realities, creating barriers for graduates and professionals to thrive within the health system. Methods Qualitative reflexive thematic analysis (RTA) was used to understand the educational and career experiences of PHPs in Nepal. Guided by principles of information power, we recruited 18 participants via purposive and snowball sampling, and semi‐structured interviews were conducted. Results Through reflexive engagement, we constructed six key themes: (1) navigating a narrow job market, (2) struggling with practical gaps, (3) barriers to job placement, (4) foundations misaligned with practice, (5) overcoming challenges, and (6) hope and future vision. The participants reported a saturated and uncertain job market, limited mentorship, inadequate practical training, nepotistic recruitment practices, and curricula misaligned with contemporary public health practices. These factors constrain employability and career satisfaction, often prompting additional study or career shifts. Despite systemic barriers, participants expressed cautious optimism that Medical Education Commission (MEC)‐led reforms, including standardized entrance examinations and integrated scholarships, together with potential vacancies at local government levels, could enhance education, improve workforce retention, and create meaningful professional roles in Nepal. Conclusions This study highlights the urgent need to realign Nepal's public health education with professional realities. Strengthening curricula with practical, competency‐based training, integrating modern technologies, providing mentorship and field exposure, and ensuring transparent employment and supportive policies can empower public health graduates and professionals. Such reforms enhance workforce resilience, career satisfaction, and professional identity, ultimately strengthening public health capacity to improve population health outcomes in resource‐constrained contexts.